Urea and limestone additions to forage sorghum silage - Bolsen, K.; Ilg, H.; Axe, D.; Smith, R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Adding urea or limestone to forage sorghum silage increased lactic and acetic acids compared with untreated silage. Urea also elevated the ensiling temperature and increased the DM loss in the silo. Although calves fed the three silages had similar performance, those fed the urea-treated silage tended to have the highest consumption but poorest feed conversion. There were no apparent improvements in silage conservation or feeding value from either urea or limestone.
Keywords: Beef; Urea; Limestone; Forage sorghum silage